2022
DOI: 10.18632/aging.204051
|View full text |Cite
|
Sign up to set email alerts
|

Ox-LDL-mediated ILF3 overexpression in gastric cancer progression by activating the PI3K/AKT/mTOR signaling pathway

Abstract: Background: This study aimed to investigate the relationship of dyslipidemia and interleukin-enhancer binding factor 3 (ILF3) in gastric cancer, and provide insights into the potential application of statins as an agent to prevent and treat gastric cancer. Methods: The expression levels of ILF3 in gastric cancer were examined with publicly available datasets such as TCGA, and western blotting and immunohistochemistry were performed to determine the expression of ILF3 in clinical specimens. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Consequently, the suppression of ILF3 resulted in decreased PD-L1, thereby enhancing the cytotoxicity of activated CD8 + T cells towards GC cells, which triggered an immune response and played a therapeutic role in GC, which align with the existing research on hepatocellular carcinoma. Previous research has demonstrated that simvastatin effectively impedes the proliferation, migration, and invasive capacity of gastric cancer cells by targeting ILF3, a potential target for statins in the treatment of gastric cancer [29]. So further exploration revealed that simvastatin effectively suppressed the expression of PD-L1 through ILF3, consequently augmenting the cytotoxicity of CD8 + T cells to GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the suppression of ILF3 resulted in decreased PD-L1, thereby enhancing the cytotoxicity of activated CD8 + T cells towards GC cells, which triggered an immune response and played a therapeutic role in GC, which align with the existing research on hepatocellular carcinoma. Previous research has demonstrated that simvastatin effectively impedes the proliferation, migration, and invasive capacity of gastric cancer cells by targeting ILF3, a potential target for statins in the treatment of gastric cancer [29]. So further exploration revealed that simvastatin effectively suppressed the expression of PD-L1 through ILF3, consequently augmenting the cytotoxicity of CD8 + T cells to GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed as previously described [29]. IHC staining was performed with ILF3, DEPTOR, mTOR, 4NHE, GPX4, PD-L1, and CD8 primary antibodies.…”
Section: Ihcmentioning
confidence: 99%
“…Tumor-derived cytokines such as IL-6 and IL-27 have promoted PD-L1+CD8+ T cells development through STAT1/STAT3 signaling ( 38 , 39 ). ILF3 promotes the production of several tumors and is closely related to cellular senescence ( 40 , 41 ). We also explored small molecules to target these transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally linked to cardiovascular health, LDL has been long recognized as a risk factor for atherosclerosis and coronary artery disease 7 . However, recent studies have expanded our comprehension of LDL, moving beyond its role in cardiovascular disease and initiating a paradigm shift in our perception of lipids' involvement in cancer biology 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…7 However, recent studies have expanded our comprehension of LDL, moving beyond its role in cardiovascular disease and initiating a paradigm shift in our perception of lipids' involvement in cancer biology. [8][9][10] The advent of transcriptomics and single-cell sequencing has revolutionized our understanding of cancer biology, offering unprecedented insights into the molecular dynamics within tumours at a resolution never before achievable. 11 Transcriptomics provides a comprehensive overview of gene expression patterns, facilitating the identification of key regulatory networks driving melanoma progression and resistance mechanisms against therapies.…”
mentioning
confidence: 99%